A micro bacteriological culture assessment of the histopathological alterations in liver and bile in gallstone disease - Jaiswal, Pradeep; Ranjan, Rajeev; Kumari, Rinku; Kumar, Kaushalendra; Rajgaria, Ria; Jha, Pawan Kumar (International Journal of Research in Medical Sciences, 2024)
Background: The present investigation aims to evaluate both the intensity and occurrence of hepatic impairment in patients afflicted with gallstone disease, examining the involvement of bacteria in the progression of these alterations. Methods: This prospective observational investigation was carried out on 189 patients scheduled for open or laparoscopic cholecystectomy at IGIMS in Patna, Bihar, India. In all the patients, laboratory and radiological investigations were performed. A healthy section of the liver border near the gallbladder fossa was chosen and grasped with non-traumatic forceps. Approximately 1 cm of the liver edge was excised using scissors and forwarded for histopathological analysis. Results: An examination of 189 liver biopsy specimens revealed that 87 (46%) patients showed no abnormalities, while 102 patients (54%) exhibited one or more changes. Upon analysing the liver biopsy samples from the control cohort (41 patients) during autopsy, 37% of the cases were identified to display hepatic lipidosis, while 48% of the cases showed lymphocytic invasion. Importantly, no cases of acute inflammatory changes were detected in the control cohort. Microbiological analysis was conducted on 96 patients, of which 33 (34%) showed positive cultures, with one or more microorganisms isolated from either the biliary tract or liver. Among these, 74% (24 cases) originated from the bile or gallbladder, while 26% (9 cases) were isolated from the liver. Conclusions: Gallstone disease induces significant liver histological changes, notably more prevalent in patients with prolonged symptoms. The present study clearly identifies this and underscores the importance of timely diagnosis and intervention for the effective management of this disease.